Integrating service fairness into the post-acceptance model of is continuance in cloud computing - Lawkobkit, Montri (2011)
This study integrates the focal determinants of service fairness into a post-acceptance model of information system continuance. This study added structural and social service fairness constructs based on Greenberg's (1993) focal determinants of organizational justice. The research model seeks to be useful in predicting satisfaction, which enhances continued usage of an IS. The results show that perceived usefulness and satisfaction influence continuance intention, as the post-acceptance model predicts. Structural service fairness significantly enhances satisfaction. However, social service fairness is not significant.